Battery
By using a pressing powder containing metal particles in the current collector of the battery and forming an oxide protective layer on its surface, the problem of insufficient battery reliability is solved, high corrosion resistance and mechanical strength are achieved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202380059650.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-06-12
- Publication Date
- 2025-03-28
Smart Images

Figure CN119731834A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to batteries. Background Art
[0002] It is expected that technologies related to the miniaturization, high performance and lamination of batteries will be developed. As such battery-related technologies, for example, Patent Document 1 discloses a battery having a current collector formed by pressing a powder for forming the current collector. The battery described in Patent Document 1 increases the contact area between the current collector and the electrode active material layer and reduces the internal resistance through this structure, thereby achieving high performance of the battery.
[0003] Prior Art Literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2009-193802 Summary of the invention
[0005] Problems to be solved by the invention
[0006] In the prior art, it is also desired to improve the reliability of batteries. Therefore, an object of the present disclosure is to improve the reliability of a battery having a current collector formed by compacting a powder.
[0007] Means for solving problems
[0008] The battery disclosed herein comprises a first electrode, a second electrode and an electrolyte.
[0009] The first electrode includes a first current collector and a first active material layer.
[0010] The first current collector is formed of a powder compact containing first metal particles.
[0011] The first metal particles each have a first protective layer provided on at least a portion of the surface of the first metal particle.
[0012] The first protective layer includes oxide.
[0013] Effects of the Invention
[0014] The present disclosure can improve the reliability of a battery including a current collector formed by compacting a powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 1 and 2 are a cross-sectional view and a plan view schematically showing the structure of the battery 1000 according to the first embodiment.
[0016] Figure 2 This is an enlarged view of the vicinity of a triple point of grain boundaries in a powder compact forming a current collector.
[0017] Figure 3It is a cross-sectional view and a plan view showing a schematic structure of a battery 1001 according to the second embodiment.
[0018] Figure 4 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1002 according to the third embodiment.
[0019] Figure 5 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1003 according to a fourth embodiment.
[0020] Figure 6 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1004 according to the fifth embodiment.
[0021] Figure 7 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1005 according to the sixth embodiment. DETAILED DESCRIPTION
[0022] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings.
[0023] The embodiments described below are all general or specific examples. The numerical values, shapes, materials, configuration positions and connection methods of the components, manufacturing processes, and the order of the manufacturing processes shown in the following embodiments are only examples and do not limit the present disclosure. In addition, the components in the following embodiments that are not recorded in the independent claims representing the highest concept are described as arbitrary components.
[0024] In the present specification, words indicating element shapes such as rectangle and numerical ranges are not strictly defined but indicate substantially equivalent ranges and include differences of, for example, several percent or so.
[0025] Each figure is a schematic diagram and does not necessarily illustrate the diagram strictly. Therefore, for example, the scales in each figure are not necessarily the same. In each figure, the same reference numerals are given to substantially the same structure, and repeated descriptions are omitted or simplified.
[0026] In this specification and the accompanying drawings, the x-axis, y-axis, and z-axis represent three axes of a three-dimensional rectangular coordinate. In each embodiment, the z-axis direction is the thickness direction of the battery. In addition, in this specification, unless otherwise specified, the "thickness direction" refers to the direction perpendicular to the surface of each layer stacked in the battery.
[0027] In this specification, “top view” refers to the state of viewing the battery along the stacking direction of each layer in the battery. “Thickness” in this specification refers to the length of the battery and each layer in the stacking direction.
[0028] In this specification, unless otherwise specified, in a battery and each layer, “side surface” refers to a surface along the stacking direction of each layer in the battery, and “main surface” refers to a surface other than the side surface.
[0029] In this specification, “inside” and “outside” in “inside” and “outside” etc. mean that when the battery is viewed along the stacking direction of each layer in the battery, the center side of the battery is the “inside” and the peripheral side of the battery is the “outside”.
[0030] In this specification, the words "upper" and "lower" in the battery structure do not refer to the upper direction (vertically above) and the lower direction (vertically below) in absolute spatial cognition, but are used as terms defined by relative positional relationships based on the stacking order in the stacking structure. In addition, the words "upper" and "lower" are not only applicable to the case where two components are spaced apart from each other and there is another component between the two components, but also to the case where two components are closely arranged and the two components are in contact.
[0031] [First embodiment]
[0032] Hereinafter, the battery according to the first embodiment will be described.
[0033] The battery of the first embodiment includes a first electrode, a second electrode and an electrolyte. The battery of the first embodiment includes a solid electrolyte layer containing, for example, a solid electrolyte as an electrolyte. The solid electrolyte layer is arranged between the first electrode and the second electrode. The first electrode includes a first current collector and a first active material layer. The first current collector is formed of a powder compact containing first metal particles. The first metal particles each have a first protective layer provided on at least a portion of the surface of the first metal particle, and the first protective layer contains an oxide.
[0034] As described above, in the battery of the first embodiment, the first current collector in the first electrode is formed of a powder compact containing first metal particles, and the first metal particles have a first protective layer containing an oxide on at least a portion of their surface. According to this structure, the first current collector can improve the corrosion resistance to gas components and solvents in the current collector formed by compacting the powder, and as a result, the reliability of the current collector can be improved. Therefore, the battery of the first embodiment can improve the reliability in the battery having the current collector formed by compacting the powder.
[0035] In addition, the first current collector is formed of a powder press. According to this structure, the first current collector is less likely to be damaged during handling than a current collector formed of a thin film of metal foil, etc., and is not prone to warping even if it is thinned. Therefore, the first current collector has higher reliability than a current collector formed of a thin film of metal foil, etc., and the thickness can be reduced while maintaining the high reliability. In addition, if the thickness of the current collector formed of a thin film of metal foil, etc. is reduced, it is easy to be damaged during handling and is also easy to warp, so it is not easy to reduce the thickness. Therefore, the battery of the first embodiment can achieve miniaturization, large capacity and high energy density compared to a battery having a current collector formed of a thin film of metal foil, etc.
[0036] As described above, the battery of the first embodiment has high reliability and can realize a thin battery with high capacity and high energy density.
[0037] In addition, the electrolyte may also be an electrolyte or other electrolyte. The electrolyte may be placed in an outer package that accommodates the first electrode and the second electrode. The battery may have a separator disposed between the first electrode and the second electrode. The separator may be an insulating material or may be impregnated with an electrolyte. In addition, the second electrode may have the same structure as the first electrode. That is, the second electrode may include a second current collector and a second active material layer, and the second current collector may have the same structure as the first current collector, that is, a structure formed by a compressed powder of a first metal particle having a first protective layer provided on at least a portion of the surface.
[0038] Hereinafter, a configuration example of the battery according to the first embodiment will be described.
[0039] Figure 1 1 and 2 are a cross-sectional view and a plan view schematically showing the structure of the battery 1000 according to the first embodiment.
[0040] Figure 1 (a) is a cross-sectional view showing a battery 1000 according to the first embodiment. Figure 1 (b) is a plan view of the battery 1000 according to the first embodiment as viewed from below in the z-axis direction. Figure 1 (a) shows Figure 1 (b) The cross section at the position indicated by line II.
[0041] like Figure 1 As shown, the battery 1000 includes a first electrode 100, a second electrode 200, and a solid electrolyte layer 300 provided between the first electrode 100 and the second electrode 200. Hereinafter, a stacked body composed of the first electrode 100, the solid electrolyte layer 300, and the second electrode 200 may be referred to as a battery element.
[0042] The first electrode 100 includes a first current collector 110 and a first active material layer 120 disposed in contact with the first current collector 110 .
[0043] The first current collector 110 is formed of a powder compact including first metal particles 111. The first metal particles 111 have a first protective layer 112 provided on at least a portion of the surface. The first protective layer 112 includes an oxide.
[0044] The second electrode 200 is disposed opposite to the first electrode 100 and is a counter electrode of the first electrode. For example, if the first electrode 100 is a positive electrode, the second electrode is a negative electrode.
[0045] The second electrode 200 includes, for example, a second current collector 210 and a second active material layer 220 disposed in contact with the second current collector 210. The second current collector 210 may have, for example, the same structure as the first current collector 110. That is, the second current collector 210 may be formed of a powder compact including first metal particles 111 having a first protective layer 112 disposed on at least a portion of the surface.
[0046] In this specification, the first current collector 110 and the second current collector 210 may be collectively referred to as “current collectors”.
[0047] In this specification, the first active material layer 120 and the second active material layer 220 may be collectively referred to as “active material layers”.
[0048] like Figure 1 As shown in (b), the first current collector 110, the first active material layer 120, the solid electrolyte layer 300, the second active material layer 220 and the second current collector 210 may all be rectangular in shape when viewed from above. In addition, the first current collector 110, the first active material layer 120, the solid electrolyte layer 300, the second active material layer 220 and the second current collector 210 may each be other shapes other than rectangular in shape when viewed from above.
[0049] Hereinafter, each structure of the battery 1000 will be described.
[0050] (Current Collector)
[0051] Hereinafter, a case where the second current collector 210 has the same structure as the first current collector 110 , that is, the second current collector 210 is also formed of a powder compact containing the first metal particles 111 will be described as an example.
[0052] The current collector is formed of a powder compact containing the first metal particles 111. The current collector formed of such a powder compact can be formed into a predetermined shape (for example, Figure 1The film-like rectangular pattern shown in the figure is formed by pressurizing the obtained film to the solid electrolyte layer 300 and bonding it. In the case of this method, for example, when the obtained film is pressurized to the solid electrolyte layer 300, a compressed powder body can be formed. In this specification, a compressed powder body refers to a material containing particles that is pressurized into a predetermined shape. The compressed powder body can be, for example, a powder material that is pressurized into a predetermined shape, and the particles are in close contact with each other.
[0053] The powder compact forming the current collector may also contain other materials besides the first metal particles 111. For example, the powder compact may also contain second metal particles containing a metal different from the metal forming the first metal particles 111. That is, the powder compact may be formed of a composite metal material containing the first metal particles 111 and the second metal particles. By having the powder compact contain the first metal particles 111 and the second metal particles, the characteristics of the current collector can be controlled in various ways. For example, by selecting the second metal particles, a current collector having properties that cannot be obtained by a single-composition metal material, such as mechanical properties, electrochemical properties, and thermal expansion coefficient, can be obtained.
[0054] When the powder compact contains the second metal particles, the second metal particles may have an average particle size smaller than the average particle size of the first metal particles 111. According to this structure, in the powder compact, it is easy to fill the second metal particles into the gaps between the first metal particles 111. Therefore, a dense current collector containing a composite metal material containing the first metal particles 111 and the second metal particles can be obtained. As a result, a current collector with suppressed resistance loss can be realized, so a higher performance battery can be provided.
[0055] Here, the average particle size of the first metal particles 111 and the second metal particles can be a value calculated from an electron microscope image of a cross section of the current collector. Specifically, the average particle size is obtained using a cutoff method based on the observed surface. The number of particles is set to 10 or more, excluding voids.
[0056] The first metal particle 111 and the second metal particle can be distinguished by the density of the reflected electron image in the SEM, or the surface analysis image of the element analysis such as SEM-EDS or EPMA. In addition, the protective layer can also be distinguished from the metal part of the metal particle by these methods. Furthermore, the density of the reflected electron image in the SEM is caused by the difference in molecular weight.
[0057] When the powder compact contains the second metal particles, the second metal particles may have a hardness different from that of the first metal particles. According to this structure, the microstructure of the composite metal material containing the first metal particles and the second metal particles can be controlled, so the filling property achieved by pressurizing the powder compact can be controlled. Therefore, the density and mechanical properties of the current collector can be controlled.
[0058] Here, the hardness of the first metal particles 111 and the second metal particles in the powder compact can be confirmed by, for example, evaluating the first metal particles 111 and the second metal particles exposed in the cross section of the current collector flattened by ion milling, etc., using micro-Vickers hardness. The larger the size of the indentation mark remaining under the same pressure, the softer it is.
[0059] The second metal particles may be softer than the first metal particles 111. In this case, by applying pressure when making the powder compact, the second metal particles may be deformed and filled preferentially to fill the gaps between the first metal particles 111. Therefore, the density of the composite metal material containing the first metal particles 111 and the second metal particles, that is, the density of the compressed body, is improved, so that a current collector with high conductivity and high corrosion resistance can be achieved. In addition, the second metal particles in the composite metal material can absorb the stress caused by the thermal expansion of the first metal particles 111 and the charge and discharge. Therefore, a current collector with high durability in cold and hot cycles and charge and discharge cycles can be obtained.
[0060] The second metal particles may be harder than the first metal particles 111. In this case, by applying pressure when making a powder compact, a fine structure containing the second metal particles between the first metal particles 111 and embedded in the first metal particles can be formed. Therefore, the second metal particles act as anchors connecting the first metal particles 111 to each other, so the bonding between the first metal particles 111 is enhanced. As a result, the durability of the collector with respect to bending (e.g., bending) stress and handling is improved, so the mechanical reliability of the collector is improved. That is, a battery with high mechanical reliability can be obtained.
[0061] The second metal particle may have a different potential from that of the first metal particle 111. According to this structure, the electrochemical stability of the current collector can be adjusted. In addition, for example, by configuring the first metal particle 111 and the second metal particle in layers, so that the current collector has, for example, a two-layer structure, it is also possible to adjust the electrochemical stability to be different on the upper and lower surfaces of the current collector. Therefore, the electrochemical stability of the current collector can be controlled according to the working potential and the charge and discharge voltage of the active material. Therefore, a highly reliable and high-performance battery can be achieved. In addition, such a two-layer structured current collector can also be used as a current collector for a bipolar electrode, for example.
[0062] Furthermore, the shape and thickness of the current collector can be arbitrarily controlled by, for example, controlling the formation by printing. The thickness of a single film can be controlled within a range of 0.1 μm to 10 μm, for example. It is also possible to repeatedly form a thick film. For example, the current collector can be a multilayer film structure formed by stacking thin films made of different materials, or different materials can be arranged on the same surface in a pattern. As an example of making the current collector a multilayer film structure, the above-mentioned example of arranging the first metal particles 111 and the second metal particles in layers, respectively, so that the current collector has, for example, a two-layer structure can be cited.
[0063] In addition, when the shape of the collector is, for example, a rectangular pattern, the corners may be cut off or formed by smooth curves without protrusions. Thus, when the printed pattern is transferred, defects such as breakage of the printed pattern generated from a portion where stress is easily concentrated (e.g., around the corners) can be reduced.
[0064] The first current collector 110 and the second current collector 210 can be partially buried in the solid electrolyte layer 300 and bonded by the pressure when stacked on the solid electrolyte layer 300. In such a buried state, the outer edge side of the current collector is bonded to the solid electrolyte layer 300, and the current collector and the solid electrolyte layer 300 can be firmly integrated.
[0065] As the metal material of the first metal particle 111, a known metal material that can be used as a current collector can be used. As the metal material of the first metal particle 111, for example, copper, silver, nickel, aluminum, palladium and gold can be used. The metal material can be a single metal or an alloy. As the metal material of the second metal particle that can be contained in the powder compact, a known metal material that can be used as a current collector can also be used. As the metal material of the second metal particle, for example, copper, silver, nickel, aluminum, palladium and gold can be used. The material of the metal particles used in the powder compact forming the current collector can be appropriately selected in consideration of not melting and decomposing under the manufacturing process, operating temperature and operating pressure, as well as the battery operating potential and conductivity applied to the current collector. The material of the current collector can also be selected based on the required tensile strength and heat resistance.
[0066] The first metal particle 111 may be a composite metal particle containing a plurality of metals having different compositions. According to this structure, in the current collector, characteristics such as corrosion resistance, thermal expansion, electrochemical stability, and mechanical reliability can be controlled. Therefore, a high-performance and high-reliability battery can be realized. The second metal particle that may be contained in the powder compact may also be a composite metal particle containing a plurality of metals having different compositions, similarly to the first metal particle 111.
[0067] The first metal particle 111 may also be a composite metal particle containing multiple metals with different potentials. This structure can control the electrochemical stability of the current collector. Therefore, a high-performance and high-reliability battery can be achieved. The second metal particle that can be included in the powder compact may also be a composite metal particle containing multiple metals with different potentials, similar to the first metal particle 111.
[0068] The thickness of the current collector is, for example, in the range of 0.3 μm to 5 μm. By increasing the thickness of the current collector, the resistance in the in-plane direction of the current collector is reduced, thereby improving the power resistance. However, by increasing the thickness of the current collector, the thermal shock resistance and the weight energy density are reduced due to the influence of the thermal expansion difference, so it can be set to an appropriate thickness value from the perspective of the overall design.
[0069] Next, the first protective layer 112 provided on at least a portion of the surface of the first metal particle 111 will be described in detail.
[0070] The first protective layer 112 covers at least a portion of the surface of the metal portion of the first metal particle 111 and contains an oxide.
[0071] The oxide contained in the first protective layer 112 may be, for example, an oxide of a metal component constituting the first metal particle 111. With this structure, in the first metal particle 111, the metal portion is firmly bonded to the oxide on its surface. Therefore, in the first metal particle 111, the bonding property between the surface of the metal portion and the first protective layer 112 is improved, so the first protective layer with excellent stability is maintained on the surface of the first metal particle. Thus, a battery with further improved reliability can be provided. Hereinafter, the surface of the metal portion of the first metal particle 111 is sometimes referred to as the metal surface of the first metal particle 111.
[0072] As the material of the first protective layer 112, a material that improves the corrosion resistance of the metal particles to gas and oxidation, etc. can be used. Oxides, especially metal oxides, are generally more stable than metals and are therefore suitable as the material of the first protective layer 112. The current collector also reaches a high temperature during the operation of the battery 1000. Therefore, an oxide with excellent high temperature stability is suitable as the material of the first protective layer 112.
[0073] The first protective layer 112 may include a metal oxide containing at least one selected from Al, Zr, Ti and Si. According to this structure, the corrosion resistance of the protective layer can be further improved. Therefore, the reliability of the collector can be improved, and as a result, a battery with further improved reliability can be provided.
[0074] The first protective layer 112 may contain an oxide other than the oxide of the metal component constituting the first metal particles 111 .
[0075] The first protective layer 112 may include, for example, an inorganic glass oxide. For example, the first protective layer 112 may be formed of an inorganic glass oxide. In addition to the inorganic glass oxide, the first protective layer 112 may also include inorganic particles. The first protective layer 112 including a glass component can further improve the stability and mechanical strength of the current collector by further including a component with high stability and a component with high mechanical strength such as inorganic particles. Examples of materials for such inorganic particles include aluminum oxide, zirconium oxide, and silicon dioxide.
[0076] The first protective layer 112 may include an amorphous body. In the case where the first protective layer 112 includes an amorphous body, the first protective layer 112 becomes softer than when it is composed only of a crystalline body. Therefore, the first protective layer 112 is easily plastically deformed. Therefore, when the first metal particle 111 is pressurized during the formation of the powder compact, the friction is reduced, the sliding between the particles is improved, and the density of the powder compact is improved. In addition, when the powder compact is formed, the first protective layer 112, which is easily deformed, is easily squeezed and moved from the bonding interface between the particles to the voids in the powder compact. Furthermore, the voids in the powder compact are, for example, voids formed between the first metal particles 111 (for example, the voids of the triple points of the grain boundaries of the first metal particles 111). As a result, the components of the first protective layer 112 that fill the voids can be increased, and the exposed surface of the first metal particle 111 can be reduced. Furthermore, the exposed surface of the first metal particle 111 refers to a surface that is not in contact with the material constituting the collector, such as the surface facing the void in the powder compact. By reducing the exposed surface of the first metal particles 111 , the corrosion resistance of the current collector is further improved, and thus a battery with further improved reliability can be provided.
[0077] The first protective layer 112 may include two or more oxides having different compositions. With this structure, the corrosion resistance of the first protective layer 112 to various gases and the like is improved, and thus the corrosion resistance of the current collector is improved. Therefore, a battery with further improved reliability can be provided.
[0078] The first protective layer 112 may be composed of a multilayer film including more than two layers. For example, the multilayer film includes thin films formed of materials different from each other. Through this structure, the corrosion resistance of the first protective layer 112 to various gases and the like is improved, so the corrosion resistance of the collector is improved. Therefore, a battery with further improved reliability can be provided. In addition, in the case where the first protective layer 112 is composed of a multilayer film, the friction between the first metal particles 111 can be changed during the pressurization process of forming the powder compact. For example, in the multilayer film, by locating the soft film on the outermost surface, the friction between the first metal particles 111 and the adjacent particles can be reduced. Therefore, the compactness of the powder compact can be improved. As a result, a current collector with low resistance and high reliability can be achieved, so a battery with further improved reliability can be provided. Furthermore, the multilayer film may include thin films formed of the same materials as each other.
[0079] In the case where the powder compact forming the current collector contains second metal particles, each second metal particle may have a second protective layer provided on at least a portion of the surface of the second metal particle. By making the powder compact contain second metal particles having a second protective layer on the surface, a current collector with better reliability can be achieved. Therefore, a battery with further improved reliability can be provided. Furthermore, the description of the material and structure of the second protective layer is the same as the description of the material and structure of the first protective layer 112, so the detailed description is omitted here.
[0080] The second protective layer may be formed of a material having a composition different from that of the first protective layer 112. With this structure, the first current collector 110 can be further provided with corrosion resistance to gas components, etc., which are different from the gas components, etc., that exhibit corrosion resistance to the first protective layer 112. Therefore, a first current collector 110 having better stability with respect to various gas components can be obtained, so a battery with further improved reliability can be provided.
[0081] The second protective layer may have a thickness different from that of the first protective layer 112. According to this structure, the first current collector 110 can be further endowed with corrosion resistance to gas components different from those exhibiting corrosion resistance in the first protective layer 112 within a wider range of conditions. Therefore, a current collector with better stability relative to various gas components can be obtained, so a battery with further improved reliability can be provided. In addition, for example, by appropriately adjusting the deformability and friction of the second protective layer, the density of the powder compact can also be controlled. Thus, a current collector with low resistance and high reliability can be achieved, so a battery with further improved reliability can be provided.
[0082] Hereinafter, the first metal particles 111 and the second metal particles may be collectively referred to as “metal particles.” In addition, the first protective layer 112 and the second protective layer may be collectively referred to as “protective layer.”
[0083] The thickness of the protective layer can be, for example, in the range of more than 1 nm and less than 50 nm. By increasing the thickness of the protective layer, the corrosion resistance of the collector is improved. However, if the thickness of the protective layer is too large, the protective layer may sometimes be peeled off from the metal surface of the metal particles due to the influence of the thermal expansion difference. Therefore, it is preferred to take the reliability of the cold and hot cycles etc. into consideration and set the thickness of the protective layer to an appropriate value.
[0084] The first protective layer 112 and the second protective layer can adopt various combinations of thickness and material. That is, the first protective layer 112 and the second protective layer can be respectively changed in thickness, changed in material composition, or changed to a variety of oxide compositions. Thus, the corrosion resistance object (e.g., gas composition) of the first protective layer 112 and the second protective layer can be adjusted, or the durability can be adjusted. By such adjustment, the durability of the collector can be further improved.
[0085] The protective layer can be formed, for example, by exposing the metal particles to air or oxygen atmosphere and applying appropriate heat treatment. The heat treatment depends on the metal material used and the particle size, and can be performed, for example, at a temperature in the range of 25°C to 500°C for a time in the range of 1 minute to 1 hour.
[0086] In the case where the protective layer contains an inorganic glass oxide, for example, a liquid polymer such as polysilazane used as a glass coating agent can be applied or impregnated into a particulate metal, and then dried and heat-treated, thereby coating the surface of the particulate metal with an inorganic glass oxide. In this case, the thickness of the protective layer can be adjusted to an arbitrary thickness in the range of 1 nm to 1 μm by using the dilution concentration of solvents such as xylene and toluene, and the number of repeated coatings of the liquid polymer. In addition, a protective layer consisting of more than two layers of multilayer films having different compositions can be formed by applying other liquid polymer materials and drying them. In addition, by mixing inorganic particles into a medium such as the above-mentioned liquid polymer or solvent, a layer structure in which a component with high stability or a component with high mechanical strength is added to the protective layer containing a glass component can also be formed. Furthermore, as materials of inorganic particles, for example, aluminum oxide, zirconium oxide, and silicon dioxide can be cited.
[0087] The crystallinity of the protective layer can also be changed by heat treatment after coating or impregnating the liquid polymer in a particulate metal. For example, by solidifying it at a relatively low temperature such as room temperature (for example, below 300°C), a protective layer containing an amorphous body can be formed. For example, the crystallinity of the protective layer can also be improved by heat treatment above 300°C. By controlling the crystallinity of such a protective layer, the hardness of the protective layer, the bonding property of the metal surface of the metal particles and the protective layer can also be adjusted, and the density and reliability of the collector can be controlled.
[0088] The protective layer can also be formed by plating a metal particle to cover it with a metal plating film, and then performing a heat treatment to convert the metal plating film into an oxide. The thickness of the metal plating film is, for example, in the range of several nanometers to about 1 μm.
[0089] The above-mentioned methods for forming the protective layer can also be combined to form a protective layer composed of two or more multilayer films having different compositions. Thus, thin films composed of different materials (e.g., oxides) having different corrosion resistance and thermal cycling characteristics can be multilayered. Therefore, the reliability of the current collector can be further improved.
[0090] As described above, by including an amorphous body in the protective layer, the protective layer is prone to plastic deformation. Therefore, when the metal particles are pressurized during the formation of the compressed body, friction is reduced, the sliding between the particles is improved, and the compactness of the powder compact is improved. In addition, such a protective layer that is easily plastically deformed is easy to move to the voids in the compressed body (for example, the voids at the triple point of the grain boundary) when the metal particles are pressurized during the formation of the compressed body. Therefore, while ensuring the conductivity between the metal particles, the voids are filled with a high concentration of the protective layer, and the conductivity and corrosion resistance of the collector are improved.
[0091] Figure 2 This is an enlarged view of the triple point of the grain boundary in the powder compact that forms the current collector. Figure 2 As shown, in the powder compact, the first protective layer 112 can be moved to the void portion of the triple point of the grain boundary and located in the void portion. For example, the volume of the first protective layer 112 can be larger in the second region of the void portion of the triple point of the grain boundary of the first metal particle 111 than in the first region of the bonding interface of two adjacent first metal particles 111. Through this structure, the electrical bonding of the bonding interface between the first metal particles 111 can be further achieved. In addition, by having a large amount of the first protective layer 112 in the second region of the void portion of the triple point of the grain boundary of the first metal particle, the component of the first protective layer 112 filling the void portion can be increased. Therefore, the exposed surface of the first metal particle 111 is reduced. As a result, a collector in which resistance loss is suppressed and corrosion resistance is improved can be achieved, so a high-performance battery with further improved reliability can be provided.
[0092] In addition, when the powder compact contains second metal particles having an average particle size smaller than that of the first metal particles, Figure 2 As shown, the second metal particles 113 are easily filled into the gaps of the triple points of the grain boundaries. Therefore, in this case, a dense current collector can be obtained.
[0093] In order to achieve Figure 2In the above structure in which the first protective layer 112 is located in the void portion of the triple point of the grain boundary, it is preferred that the crystallinity of the outermost surface of the first protective layer 112 is low. In addition, in the case of containing the second metal particles 113, the crystallinity can be changed in the first protective layer 112 and the second protective layer. Thus, the densification process relative to pressure can be controlled over a wide range, and a more stable and dense collector can be formed relative to the pressurization rate and pressurization temperature. The crystallinity of the protective layer can be reduced, for example, by repeatedly performing collisions between powders to deform the atomic arrangement on the surface. For example, in such an application, a general powder processing device such as a ball mill or a mixer can be used. Only metal particles can be placed in a container made of polyethylene for processing, and a pulverizing medium such as zirconia balls can be appropriately placed, and water or ethanol can also be added. Thus, the collision energy can be adjusted.
[0094] The crystallinity and thickness of the protective layer can be obtained by observing the cross section of the metal particles or the pressed powder after ion milling with high resolution TEM or SEM. For example, the crystallinity and thickness of the protective layer can be obtained by observing the lattice image, the disordered atomic arrangement state and the physical thickness of the region with high resolution TEM or SEM. In addition, the hardness of the protective layer is the same as the hardness of the metal particles, and the cross section of the collector cut flatly by ion milling or the like can be used to evaluate and compare by methods such as micro-Vickers hardness.
[0095] In addition, from the perspective of making the pressed powder firm, the metal surface of the metal particle can be a concave-convex surface with an increased bonding area. Thus, not only can the bonding between particles and the difficulty of peeling the protective layer be improved, but also the bonding between the collector and the solid electrolyte layer 300, and the bonding between the collector and the first active material layer 120 or the second active material layer 220 can be improved. In this case, the surface roughness of the metal surface of the metal particle can be, for example, Rz = 0.1μm to 1μm. The concave-convex surface of the metal particle can be formed by collision between metal particles before forming a protective layer, or by mixing hard particles (such as SiC particles) with a particle size below the target Rz value into the metal particles before forming the protective layer. In addition, by using a particle compounding device such as "Nobilta" made by Hosokawa Micron Co., Ltd. that can apply shear stress between particles to impact and collide between particles, the metal surface of the metal particle can also be roughened. In addition, by treating the fine-particle oxide as the composition of the protective layer with a particle composite device, a protective layer is formed on the metal particles, and a concave-convex surface can also be formed at the same time. In addition, the surface roughness of the first metal particle and the second metal particle can also be set to be different from each other. Thus, the surface shape can be adjusted according to the difference in the mechanical properties of the first metal particle and the second metal particle, so the bonding property of the composite metal material containing two kinds of metal particles can be further improved. Through the surface roughness of the first metal particle and the second metal particle, the interfacial bonding property between the particles becomes firm, and a battery with high reliability for expansion and contraction of cold and hot cycles and charge and discharge cycles can be realized.
[0096] The current collector may further contain a resin component. The resin component may be, for example, a binder component added to a material containing metal particles when the powder compact is formed. With this structure, the mechanical strength of the current collector and the bonding property with the active material layer are enhanced. Therefore, a battery with high reliability against external stresses such as bending or impact can be obtained.
[0097] The current collector may contain at least one selected from a Si-containing component and a F-containing component. The Si-containing component and the F-containing component may be, for example, a resin component. According to this structure, a current collector having high heat resistance and corrosion resistance can be realized. In addition, for rapid temperature changes, the difference in thermal expansion coefficients at the bonding interface between the Si-containing component or the F-containing component (for example, a resin component) and the metal particles can be absorbed by the softness of the Si-containing component or the F-containing component. Therefore, the Si-containing component or the F-containing component is not easily peeled off from the first current collector, and the high heat resistance and corrosion resistance of the current collector can be maintained. Therefore, a battery with high reliability for battery heating caused by high-rate operations such as rapid charging and discharging can be realized.
[0098] At least one selected from the above-mentioned Si-containing component and F-containing component can be included in the current collector by, for example, attaching at least one selected from silicone resin and fluorine resin to the powder compact. For example, by bringing a thin layer of silicone resin or fluorine resin formed as a release agent on a polyethylene terephthalate (PET) film into contact with the powder compact when the powder compact is formed and applying pressure, the Si-containing component and the F-containing component can be transferred to a thickness of, for example, 5 nm to 10 nm within a range that does not affect conductivity.
[0099] In a current collector containing at least one selected from a Si-containing component and a F-containing component prepared by the above method, for example, the total volume concentration of the Si-containing component and the F-containing component is higher in the interface between the current collector and the active material layer than in the interior of the current collector. According to this structure, the reliability of the interface between the current collector and the active material layer, which has the highest ion mobility density and is easy to generate heat, is improved, so that a battery with further improved reliability can be obtained. Furthermore, the volume concentration of the Si-containing component and the F-containing component in the current collector can be obtained, for example, by the following method: using the SEM image of the cross section of the current collector, etc., and calculating the area of the Si-containing component and the F-containing component in the image by image analysis. That is, the area of the cross section of the collector is regarded as the volume, and the volume concentration can be calculated. In addition, the Si-containing component and the F-containing component can be distinguished from other components according to the density of the reflected electron image in the SEM, or the surface analysis image of the elemental analysis such as SEM-EDS or EPMA. Regarding the volume concentration of Si-containing components and F-containing components, for example, the interface between the collector and the active material layer is taken as the surface area of the collector with a thickness of 50 nm from the interface between the collector and the active material layer (i.e., the surface of the collector), and the area outside the surface area is taken as the interior of the collector.
[0100] (Active material layer)
[0101] The first active material layer 120 is, for example, a positive electrode active material layer. The first active material layer 120 is sandwiched between the first current collector 110 and the solid electrolyte layer 300 . The first active material layer 120 may be in contact with the first current collector 110 . The first active material layer 120 may be in contact with the solid electrolyte layer 300 .
[0102] The second active material layer 220 is, for example, a negative electrode active material layer. The second active material layer 220 is sandwiched between the second current collector 210 and the solid electrolyte layer 300 . The second active material layer 220 may be in contact with the second current collector 210 . The second active material layer 220 may be in contact with the solid electrolyte layer 300 .
[0103] The positive electrode active material layer contains a positive electrode active material.
[0104] The positive electrode active material is a material that inserts or removes metal ions such as lithium (Li) ions or magnesium (Mg) ions in the crystal structure at a higher potential than the negative electrode, and then undergoes oxidation or reduction. The type of positive electrode active material can be appropriately selected according to the type of battery, and a known positive electrode active material can be used.
[0105] The positive electrode active material is, for example, a compound containing lithium and a transition metal element, such as an oxide containing lithium and a transition metal element, or a phosphate compound containing lithium and a transition metal element.
[0106] Examples of oxides containing lithium and transition metal elements include LiNi x M 1-x Lithium nickel composite oxides such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or lithium manganese oxide having a spinel structure (such as LiMn2O4, Li2MnO3 or LiMnO2).
[0107] An example of a phosphate compound containing lithium and a transition metal element is lithium iron phosphate (LiFePO 4 ) having an olivine structure.
[0108] As the positive electrode active material, sulfides such as sulfur (S) and lithium sulfide (Li2S) may be used. In this case, lithium niobate (LiNbO3) or the like may be coated or added to the positive electrode active material particles.
[0109] As the positive electrode active material, only one of these materials may be used, or two or more of these materials may be used in combination.
[0110] In order to improve lithium ion conductivity or electronic conductivity, the positive electrode active material layer may contain materials other than the positive electrode active material in addition to the positive electrode active material. That is, the positive electrode active material layer may be a mixture layer. Examples of such materials include solid electrolytes such as inorganic solid electrolytes and sulfide solid electrolytes, conductive additives such as acetylene black, or adhesives such as polyethylene oxide and polyvinylidene fluoride.
[0111] The positive electrode active material layer can have a thickness of, for example, 5 μm or more and 100 μm or less.
[0112] The negative electrode active material layer contains a negative electrode active material.
[0113] The negative electrode active material layer is a layer mainly composed of negative electrode materials such as negative electrode active material.
[0114] The negative electrode active material is a material that inserts or removes metal ions such as lithium (Li) ions or magnesium (Mg) ions in the crystal structure at a lower potential than the positive electrode, and then undergoes oxidation or reduction. The type of negative electrode active material can be appropriately selected according to the type of battery, and a known negative electrode active material can be used.
[0115] Examples of negative electrode active materials include carbon materials such as natural graphite, artificial graphite, graphite carbon fiber, and resin sintered carbon, or alloy materials mixed with solid electrolytes. Examples of alloy materials include LiAl, LiZn, Li3Bi, Li3Cd, Li3Sb, Li4Si, Li 4.4 Pb、Li 4.4 Sn、Li 0.17 Lithium alloys such as LiC6, lithium titanate (Li4Ti5O 12 ) and oxides of transition metal elements such as zinc oxide (ZnO) or silicon oxide (SiO x ) and other metal oxides.
[0116] The negative electrode active material may be made of only one of these materials or a combination of two or more of these materials.
[0117] In order to improve lithium ion conductivity or electronic conductivity, the negative electrode active material layer may contain materials other than the negative electrode active material in addition to the negative electrode active material. Examples of such materials include solid electrolytes such as inorganic solid electrolytes and sulfide solid electrolytes, conductive additives such as acetylene black, or adhesives such as polyethylene oxide and polyvinylidene fluoride.
[0118] The negative electrode active material layer can have a thickness of, for example, 5 μm or more and 100 μm or less.
[0119] like Figure 1 As shown in (b), the active material layer is rectangular in plan view, but is of course not limited thereto. The active material layer may be circular or elliptical as long as it includes a portion in contact with the current collector. In addition, the active material layer may be larger or smaller than the current collector in plan view.
[0120] (Solid electrolyte layer)
[0121] The solid electrolyte layer 300 includes a solid electrolyte.
[0122] The solid electrolyte layer 300 contains, for example, a solid electrolyte as a main component. Here, the main component refers to a component that is contained in the largest amount by mass ratio in the solid electrolyte layer 300. The solid electrolyte layer 300 may also be composed of only a solid electrolyte.
[0123] The solid electrolyte may be any known solid electrolyte for batteries as long as it has ion conductivity. As the solid electrolyte contained in the solid electrolyte layer 300, for example, a solid electrolyte that conducts metal ions such as lithium ions or magnesium ions can be used.
[0124] As the solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte can be used.
[0125] Sulfide-based solid electrolytes include, for example, Li2S-P2S5 system, Li2S-SiS2 system, Li2S-B2S3 system, Li2S-GeS2 system, Li2S-SiS2-LiI system, Li2S-SiS2-Li3PO4 system, Li2S-Ge2S2 system, Li2S-GeS2-P2S5 system or Li2S-GeS2-ZnS system.
[0126] Oxide-based solid electrolytes include, for example, lithium-containing metal oxides, lithium-containing metal nitrides, lithium phosphate (Li3PO4), or lithium-containing transition metal oxides. Examples of lithium-containing metal oxides include Li2O-SiO2 or Li2O-SiO2-P2O5. Examples of lithium-containing metal nitrides include Li x P y O 1-z N z (0<z≤1) An example of the lithium-containing transition metal oxide is lithium titanium oxide.
[0127] The halogenated solid electrolyte includes, for example, a compound containing Li, M, and X. Here, M is at least one selected from metal elements and metalloid elements other than Li. X is at least one selected from F, Cl, Br, and I.
[0128] "Metalloid elements" are B, Si, Ge, As, Sb and Te. "Metallic elements" are all elements contained in Groups 1 to 12 of the periodic table (except hydrogen) and all elements contained in Groups 13 to 16 of the periodic table (except B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se).
[0129] In order to improve the ion conductivity of the halide solid electrolyte, M may contain Y. M may also be Y.
[0130] The halide solid electrolyte may be composed of, for example, Li a Me b Y c The compound represented by X6 satisfies the formulas a+mb+3c=6 and c>0. The value of m represents the valence of Me.
[0131] In order to improve the ionic conductivity of the halide solid electrolyte, Me may be at least one selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb.
[0132] In order to improve the ion conductivity of the halide solid electrolyte, X may contain at least one selected from Cl and Br.
[0133] The halide solid electrolyte may contain, for example, at least one selected from Li3YCl6 and Li3YBr6.
[0134] As the solid electrolyte, only one of these materials may be used, or two or more of these materials may be used in combination.
[0135] Solid electrolyte layer 300 may contain a bonding agent such as polyethylene oxide or polyvinylidene fluoride in addition to the solid electrolyte.
[0136] Solid electrolyte layer 300 may have a thickness of 5 μm or more and 150 μm or less.
[0137] The material of the solid electrolyte may be composed of an aggregate of particles or a sintered structure.
[0138] The battery 1000 of the first embodiment includes the first current collector 110 having the structure described above, and can form a patterned current collector that is difficult to form with a current collector made of metal foil with high reliability. Therefore, the battery 1000 of the first embodiment can realize various battery packs such as large-capacity batteries connected in parallel or in series by a stacking process.
[0139] Comparing the structure of the battery 1000 of the first embodiment with the structure of the battery described in Patent Document 1, there are the following differences.
[0140] Patent document 1 discloses a battery formed by compacting a current collector having conductivity. However, the current collector formed by metal particles without the above-mentioned protective layer has weak corrosion resistance to gas or moisture, etc., and may, for example, cause oxidation and sulfidation of the particle surface. Therefore, at the particle interface, the conductivity between particles deteriorates. In addition, at the particle interface, stress is generated due to the expansion of the modified surface layer, so it becomes brittle and the mechanical strength is reduced. Furthermore, the expansion of the modified surface layer includes, for example, volume expansion due to oxidation or sulfidation. In this way, the battery described in patent document 1 has the problem of insufficient reliability of the current collector. In contrast, the battery 1000 of the first embodiment has a current collector formed by a powder compact having high corrosion resistance due to metal particles having a protective layer on the surface. Therefore, in the battery 1000 of the first embodiment, the reduction of conductivity and mechanical strength can be suppressed, and high reliability can be achieved.
[0141] [Second embodiment]
[0142] Hereinafter, a battery according to a second embodiment will be described, and matters described in the first embodiment will be omitted as appropriate.
[0143] Figure 3 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1001 according to the second embodiment.
[0144] Figure 3 (a) is a cross-sectional view of a battery 1001 according to the second embodiment. Figure 3 (b) is a plan view of the battery 1001 according to the second embodiment as viewed from below in the z-axis direction. Figure 3 (a) shows Figure 3 (b) is a cross-sectional view taken along the dotted line III-III.
[0145] like Figure 3 As shown, the battery 1001 further includes a cover layer 400 in addition to the structure of the battery 1000 of the first embodiment.
[0146] The cover layer 400 functions as a layer that protects the battery element of the battery 1001 from impact and environmental influences. Therefore, the reliability of the battery 1001 can be further improved.
[0147] The covering layer 400 can be formed of a powder compact, for example. When the covering layer 400 is formed of a powder compact, the particles on the surface act as anchors, and high bonding properties with the current collector formed of the powder compact can be obtained. In addition, according to this structure, the force acting on the interface between the covering layer 400 and the current collector is easily dispersed. Therefore, with this structure, the interface peeling between the covering layer 400 and the current collector can be suppressed.
[0148] The cover layer 400 is provided on at least one of the first electrode 100 and the second electrode 200 .
[0149] like Figure 3 As shown, the cover layer 400 may be disposed on both the first electrode 100 and the second electrode 200 .
[0150] The material of the cover layer 400 may be a solid electrolyte. The cover layer 400 may include, for example, the solid electrolyte constituting the solid electrolyte layer 300. Since the cover layer 400 includes the same material as the battery element, the thermal expansion coefficients of the cover layer and the battery element are close. As a result, the durability of the battery 1001 is improved for firing in the manufacturing process of the battery 1001, changes in ambient temperature when the battery 1001 is used, and hot and cold cycles.
[0151] The cover layer 400 may include a material different from that of the battery element.
[0152] The material of the covering layer 400 may be an insulating material. Examples of insulating materials include inorganic ceramic materials or resin materials. Examples of inorganic ceramic materials include aluminum oxide or boron nitride. Examples of resin materials include epoxy resins. In the case where the covering layer 400 includes aluminum oxide or boron nitride having excellent thermal conductivity, even if the battery 1001 is enlarged, the influence of the thermal expansion difference within the battery element can be reduced. Therefore, a battery 1001 that is excellent in thermal shock resistance can be realized. Epoxy resins are light in weight. Therefore, in the case where the covering layer 400 contains epoxy resins, the reduction in the weight energy density of the battery 1001 can be suppressed. In addition, the resin material is generally softer than the constituent components of the battery element in the battery 1001. Therefore, the impact resistance of the battery 1001 is improved by the cushioning property of the resin material.
[0153] When the cover layer 400 is disposed on both the first electrode 100 and the second electrode 200, the cover layer 400 may have the same thickness on both electrodes. Thus, during compression during lamination or shrinkage during firing in the manufacturing process of the battery 1001, stresses on the upper and lower cover layers 400 are balanced, thereby suppressing structural defects such as warping and cracking of the battery 1001.
[0154] The thickness of the cover layer 400 is, for example, not less than 100 μm and not more than 500 μm.
[0155] The covering layer 400 can be formed, for example, by transferring the precursor of the covering layer 400 under pressure to the surface of the collector, the precursor of the covering layer 400 being formed by applying a slurry containing the material of the covering layer 400 on a PET film. In addition, the precursor of the covering layer 400 formed by applying the slurry containing the material of the covering layer 400 is equivalent to a molded body called a green sheet in the technical field of a multilayer ceramic capacitor (MLCC), for example. For example, a silicone resin is pre-coated on the surface of the PET film, and then a slurry containing the material of the covering layer 400 such as a solid electrolyte slurry is applied. The thickness of the silicone resin applied on the surface of the PET film is, for example, in the range of 10 nm or more and 50 nm or less. In this case, the silicone resin component remains on the surface of the precursor of the covering layer 400 transferred to the collector (i.e., the surface peeled from the PET film). Therefore, the surface of the collector including the plated film is covered with the covering layer 400 containing the silicone resin component. The silicone-based resin component is chemically stable and therefore imparts a rust-proof effect to the surface of the current collector in contact with the silicone-based resin component.
[0156] The silicone-based resin component can be detected as a region having a higher silicon (Si) concentration than other parts when the cross section after ion milling is analyzed by a composition analysis method such as electron probe microanalyzer (EPMA).
[0157] As another method for forming the cover layer 400 , for example, a paste containing the material of the cover layer 400 may be printed on the current collector using a metal mask or a screen printing plate.
[0158] A mark indicating polarity such as the positive electrode and the negative electrode may be printed on the cover layer 400. The shape of the mark is not particularly limited, and for example, a circular or rectangular mark may be printed. Alternatively, a hole may be provided on the cover layer 400 and used as a mark. In this way, the positive and negative electrodes of the battery can be distinguished from the appearance.
[0159] The positive electrode and the negative electrode can be distinguished by including a pigment in the cover layer 400 .
[0160] [Third Embodiment]
[0161] Hereinafter, a battery according to a third embodiment will be described. Matters described in the above embodiments will be omitted as appropriate.
[0162] Figure 4 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1002 according to the third embodiment.
[0163] Figure 4 (a) is a cross-sectional view of a battery 1002 according to the third embodiment. Figure 4(b) is a plan view of the battery 1002 according to the third embodiment as viewed from below in the z-axis direction. Figure 4 (a) shows Figure 2 (b) The cross section at the position indicated by line IV-IV.
[0164] The battery 1002 further includes terminal electrodes 500a and 500b in addition to the structure of the battery 1001 of the second embodiment. The terminal electrode 500a is electrically connected to the first electrode 100. Specifically, the terminal electrode 500a is electrically connected to the first current collector 110. The terminal electrode 500b is electrically connected to the second electrode 200. Specifically, the terminal electrode 500b is electrically connected to the second current collector 210. Hereinafter, the terminal electrode 500a and the terminal electrode 500b are sometimes collectively referred to as "terminal electrodes".
[0165] The terminal electrode includes, for example, a metal conductor. Examples of the metal conductor include Ag or Cu. Ag and Cu have high electrical conductivity and thus can reduce the resistance loss of the battery 1002.
[0166] The terminal electrode can be formed of a material containing metal powder and resin such as a conductive resin. Examples of the metal powder include Ag or Cu listed as examples of the above-mentioned metal conductor. With such a terminal electrode, a small and surface-mounted high-performance battery can be realized.
[0167] The surface of the terminal electrode can be plated. That is, the battery 1002 of the third embodiment can have a plating film on the surface of the terminal electrode. By providing a plating film on the surface of the terminal electrode, a strong and low-resistance connection with the mounting substrate can be achieved. In addition, since it is possible to suppress the penetration of moisture and gas that deteriorates the battery into the power generation element, the reliability of the battery can be improved. Therefore, a small and high-performance surface-mounted battery can be achieved. On the surface of the terminal electrode, a plating treatment with good solder wettability such as Sn is performed, such as by electrolytic plating. As a result, soldering and mounting can be performed through a general reflow process. The thickness of the plating film formed on the surface of the terminal electrode is, for example, greater than 1 μm and less than 5 μm.
[0168] [Fourth embodiment]
[0169] Hereinafter, a battery according to a fourth embodiment will be described. Matters described in the above embodiments will be omitted as appropriate.
[0170] Figure 5 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1003 according to a fourth embodiment.
[0171] Figure 5 (a) is a cross-sectional view of a battery 1003 according to the fourth embodiment. Figure 5(b) is a plan view of the battery 1003 according to the fourth embodiment as viewed from below in the z-axis direction. Figure 5 (a) shows Figure 5 (b) The cross section at the position indicated by line VV.
[0172] The battery 1003 has a structure different from that of the battery 1002 of the third embodiment in that the shapes of the first current collector and the second current collector are different. Figure 5 As shown, the thickness of the outer edge portion 114a of the first current collector 114 when viewed from above is greater than the thickness of the center portion 114b of the first current collector 114 when viewed from above. As a result, when the terminal electrode 500a is connected to the outer edge portion 114a of the first current collector 114, the connection area is increased. Therefore, the connection resistance between the first current collector 114 and the terminal electrode 500a can be reduced. Furthermore, the fixity between the first current collector 114 and the terminal electrode 500a is also improved. The first current collector 114 having such a shape can be realized, for example, by using a powder compact having a thickness corresponding to the outer edge portion 114a greater than the thickness corresponding to the center portion 114b. By using a powder compact having such a thickness shape, for example, during the process of transferring the collector printed film, the printed film can be prevented from cracking from the outer edge portion. Therefore, defects of the first current collector 114 can also be suppressed. Therefore, a battery 1003 with high performance and excellent reliability can be realized.
[0173] The thickness of the first current collector 114 near the connection portion with the terminal electrode 500a can be greater than the thickness of other portions. The connection between the first current collector 114 and the terminal electrode 500a becomes stronger, and the reliability against bending stress is improved. In addition, the connection resistance between the first current collector 114 and the terminal electrode 500a can be further reduced.
[0174] For example, in the first current collector 114 , a region having a thickness approximately twice that of the center portion 114 b may be formed over a width of 100 μm from the end portion of the connection portion with the terminal electrode 500 a .
[0175] The second current collector 214 may be thicker at the outer edge 214a than at the center 214b in plan view, similarly to the first current collector 114. Also, the second current collector 214 may be thicker near the connection portion with the terminal electrode 500b than at other portions.
[0176] Hereinafter, the outer edge portion of the current collector which is thicker than the central portion is referred to as a thick film portion.
[0177] The thick film portion of the current collector can be a material different from that of the first current collector 114 and the second current collector 214. The material of the thick film portion of the current collector only needs to be conductive. Preferably, a material that is easily electrically connected to the terminal electrode is used. Examples of materials for the thick film portion of the current collector include Au, Ag, Cu, Al, Ni, Fe, Pd, or Pt. Among these materials, a variety of conductive materials can be mixed and used, and alloys can also be used. In this way, the thermal expansion coefficient or mechanical properties of the collector can be adjusted to improve the heat shock resistance or mechanical reliability of the collector.
[0178] The width of the thick film portion may be, for example, greater than the width of the portion of the terminal electrode 500a located on the main surface of the battery 1003. As a result, the stress load concentrated near the terminal electrode during bending is dispersed and reduced in the protruding range of the thick film portion. As a result, it is possible to suppress the terminal electrode 500a from breaking at the end of the main surface of the battery 1003 of the terminal electrode 500a. In addition, the so-called protruding range of the thick film portion, for example, in the case of the first current collector 114, refers to the protruding range of the thick film portion at the end of the main surface of the battery 1003. Figure 5 The range indicated by reference numeral 114c in (a) is the range of the thick film portion extending toward the inside of the battery 1003 from the end of the main surface of the battery 1003 of the terminal electrode 500a.
[0179] The thick film portion of the current collector can be realized, for example, by locally printing a current collector forming paste containing the first metal particles thickly. The thick portion can be realized, for example, by repeatedly printing a current collector forming paste containing the first metal particles. In the case of forming a thick film portion by repeated printing in this way, the film can be thickened while relieving the stress during film formation, thereby reducing the peeling and warping of the current collector from the active material layer. The current collector formed by repeated multiple printings can be detected by cross-sectional observation using SEM or the like, and a layered stripe pattern can be detected.
[0180] The thick film portion of the current collector may have a thickness of, for example, 10 μm or more.
[0181] According to the above configuration, the connection resistance between the current collector and the terminal electrode can be reduced, and a battery with further suppressed resistance loss can be realized.
[0182] [Fifth embodiment]
[0183] Hereinafter, a battery according to a fifth embodiment will be described. Matters described in the above embodiments will be omitted as appropriate.
[0184] Figure 6 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1004 according to the fifth embodiment.
[0185] Figure 6 (a) is a cross-sectional view of a battery 1004 according to the fifth embodiment. Figure 6(b) is a plan view of the battery 1004 according to the fifth embodiment as viewed from below in the z-axis direction. Figure 6 (a) shows Figure 6 (b) The cross section at the position indicated by the VI-VI line.
[0186] like Figure 6 As shown, the battery 1004 is formed by arranging different materials on the same surface in a pattern on the basis of the structure of the battery 1002 of the third embodiment. In the battery 1004 of the fifth embodiment, the first current collector 115 is formed by a portion 115a and a portion 115b, the portion 115a is formed by a powder compact containing first metal particles, and the portion 115b is formed by a powder compact containing second metal particles. The portion 115b formed by the powder compact containing the second metal particles forms a connection portion with the terminal electrode 500a of the first current collector 110. The portion 115a formed by the powder compact containing the first metal particles forms a portion other than the above-mentioned connection portion.
[0187] In the battery 1004 of the fifth embodiment, the first metal particle can be formed of Ag, for example, and the second metal particle can be formed of Pd, for example. In this way, the connecting portion is formed by a powder compact containing Pd particles, and an alloy (for example, an Ag-Pd alloy) is generated around the connecting portion by heat treatment when forming the terminal electrode 500a containing Ag. As a result, an alloy bonding layer is formed at the connecting portion of the first current collector 115 and the connecting portion of the terminal electrode 500a, and the first current collector 115 is firmly and low-resistance connected to the terminal electrode 500a. In this way, the metal material of the second metal particle used in the connecting portion can use a metal that forms an alloy with the terminal electrode. The heat treatment for generating the alloy can be performed, for example, in a belt furnace or a general sintering furnace, or a soldering iron or iron corresponding to a local high temperature that only heats the connecting portion can be used.
[0188] With the above structure, the connection portion of the first current collector 115 and the terminal electrode 500a can be firmly fixed even in the case of thermal cycles and shocks, so that the resistance between the first current collector 115 and the terminal electrode 500a can be kept low. Therefore, a high-performance and highly reliable battery 1004 can be realized.
[0189] The second current collector 215 may also be formed by arranging different materials on the same surface in a pattern, similar to the first current collector 115. For example, the connection portion of the second current collector 215 with the terminal electrode 500b (the region indicated by the symbol 215b in the figure) may be a powder compact containing the second metal particles, and the portion other than the connection portion (the region indicated by the symbol 215a in the figure) may be a powder compact containing the first metal particles.
[0190] [Sixth embodiment]
[0191] Hereinafter, a battery according to a sixth embodiment will be described. Matters described in the above embodiments will be omitted as appropriate.
[0192] Figure 7 It is a cross-sectional view and a plan view showing a schematic structure of a battery 1005 according to the sixth embodiment.
[0193] Figure 7 (a) is a cross-sectional view of a battery 1005 according to the sixth embodiment. Figure 7 (b) is a plan view of the battery 1005 according to the sixth embodiment as viewed from below in the z-axis direction. Figure 7 (a) shows Figure 7 (b) The cross section at the position indicated by the VI-VI line.
[0194] like Figure 7 As shown, the battery 1005 has a structure in which a plurality of battery elements (i.e., single battery cells) are stacked. The plurality of single batteries can be connected in series.
[0195] The battery 1005 includes, for example, a bipolar electrode 600 that connects a plurality of single cells.
[0196] The current collector 601 of the bipolar electrode 600 is composed of two layers of powder compacts having different compositions. Specifically, for example, the current collector 601 has a structure composed of a layer 601a and a layer 601b, wherein the layer 601a is formed of a powder compact containing a first metal particle, and the layer 601b is formed of a powder compact containing a second metal particle. In this way, by arranging the first metal particle and the second metal particle in layers to form a two-layer structure, the electrochemical stability on the upper and lower surfaces of the current collector 601 is different. For example, the current collector 601 can be formed by transferring a printed film formed by two printings in a manner that the metal of the metal particles on the positive electrode side is Al and the metal of the metal particles on the negative electrode side is Ni. In addition, two printed films can be made separately and stacked by transfer.
[0197] There is no particular limitation on the printing method. For example, it can be formed by screen printing, printing a paste containing Al particles with a protective layer and a paste containing Ni particles with a protective layer. It is also possible to prepare two pastes separately, and press-transfer the materials printed with each paste on a PET film coated with a silicone or fluorine resin release agent with a thickness of 10nm to 50nm to form a collector. As a result, since the Si-containing component or the F-containing component can also be transferred and included in the collector, the corrosion resistance of the collector is further improved.
[0198] In this way, a current collector having a multilayer structure in which two layers of different compressed powder bodies are bonded to each other on the inside and outside can form a bipolar electrode 600 with an electrochemically stable combination. In the bipolar electrode 600 of this structure, the bonding of layer 601a and layer 601b is carried out between the particles forming each compressed powder body, so the bonding reliability is improved and the connection resistance between two different metal layers is also reduced. In addition, in the compressed powder body of the multilayer structure, the thickness of each layer and the material composition of the layer can be arbitrarily set from the perspective of electrochemical stability, mechanical strength or heat resistance. In addition, it can also be a multilayer of compressed powder bodies with the same composition but different particle shapes. Thus, it is also possible to control the bonding properties with the adjacent active material layers or the resistance loss of the bonding interface. Through such a structure, a bipolar electrode with low resistance and high reliability can be formed, so a multilayer battery connected in series with high performance and excellent reliability can be realized.
[0199] [Battery manufacturing method]
[0200] Next, an example of a method for manufacturing the battery of this embodiment will be described. Hereinafter, a method for manufacturing the battery 1000 of the first embodiment will be described.
[0201] Hereinafter, an example in which the first electrode 100 is a positive electrode and the second electrode 200 is a negative electrode will be described.
[0202] First, each paste used in printing and forming the positive electrode active material layer and the negative electrode active material layer is prepared. As a solid electrolyte used in the mixture of the positive electrode active material layer and the negative electrode active material layer, for example, a glass powder of Li2S-P2S5-based sulfide with an average particle size of about 1 μm and containing triclinic crystals as the main component is prepared. The glass powder has, for example, 3×10 -3 S / cm~4×10 -3 S / cm ion conductivity.
[0203] As the positive electrode active material, for example, a layered Li·Ni·Co·Al composite oxide (LiNi 0.8 Co 0.15 Al 0.05 O2) powder.
[0204] A positive electrode active material layer paste is prepared by dispersing a mixture containing the positive electrode active material and the glass powder in an organic solvent or the like.
[0205] A solid electrolyte layer slurry for forming a solid electrolyte layer is prepared by dispersing a mixture containing the above-mentioned glass powder in an organic solvent or the like.
[0206] As the negative electrode active material, for example, natural graphite powder having an average particle size of about 3 μm is used. A negative electrode active material layer paste is prepared by dispersing a mixture containing the negative electrode active material and the glass powder in an organic solvent or the like.
[0207] Next, as materials for the positive electrode collector and the negative electrode collector, for example, Al particles having a protective layer on the surface and Ni particles having a protective layer on the surface are prepared respectively. The average particle size of the Al particles is, for example, 1.0 μm. The average particle size of the Ni particles is, for example, 0.3 μm. The protective layer can be formed in advance from SiO2 glass (amorphous body) by, for example, spraying polysilazane onto a metal conductor particle powder with a two-fluid nozzle while vibrating and drying the metal particles at about 100°C. The thickness of the protective layer formed in this way is, for example, in the range of 1 nm to 10 nm. A positive electrode collector material and a negative electrode collector material containing such metal particles having a protective layer on the surface are dispersed in an organic solvent or the like together with a binder component to prepare a positive electrode collector paste and a negative electrode collector paste.
[0208] Use the solid electrolyte layer slurry to form a solid electrolyte layer sheet. For example, the solid electrolyte layer slurry is molded into a sheet with a thickness of about 10μm to 50μm by a die coater. The molded sheet can be multilayered. On the surface and back of the solid electrolyte layer sheet prepared in this way, the positive electrode active material layer paste and the negative electrode active material layer paste are respectively applied in a predetermined shape and a thickness of about 50μm to 100μm. The positive electrode active material layer paste and the negative electrode active material layer paste are air dried at 80°C to 130°C to a thickness of 30μm to 60μm.
[0209] The paste for the positive electrode collector and the paste for the negative electrode collector are printed in a predetermined pattern on a PET film pre-coated with a silicone resin, for example, with a thickness of 10nm to 30nm, to form a positive electrode collector and a negative electrode collector. Next, the positive electrode collector and the negative electrode collector printed on the PET film are heated and pressurized to peel them off the PET film, and each collector is transferred to the pattern of the dried positive electrode active material layer paste and the pattern of the negative electrode active material layer paste. The silicone resin component adheres to the surface of the collector during transfer, which plays a rust-proof role for the collector. In addition, the collector is in a concave-convex surface state with a surface roughness of, for example, Rz=1μm to 5μm, and its rough surface can improve the bonding with the solid electrolyte layer and the active material layer. In this way, a laminated body is obtained in which a positive electrode as the first electrode, a solid electrolyte layer, and a negative electrode as the second electrode are sequentially formed.
[0210] Next, the material is pressed by a press machine at a temperature of about 70°C and a pressure of 1 t / cm 2 ~3t / cm 2The laminated body of the battery 1000 is pressurized with a pressure of , and further, the laminated body may be subjected to heat treatment, sintering, hydrostatic pressing, etc., as required, in order to increase density, strength, and characteristics.
[0211] In addition, a method for manufacturing a single-piece battery element has been described here, but for example, a printed pattern (current collector) of a plurality of battery elements may be transferred onto a solid electrolyte layer and then cut into individual pieces to manufacture a plurality of batteries.
[0212] [Other embodiments]
[0213] (Note)
[0214] The following technical solutions are disclosed through the description of the above embodiments.
[0215] (Technical Solution 1)
[0216] A battery comprises a first electrode, a second electrode and an electrolyte, wherein the first electrode comprises a first current collector and a first active material layer, the first current collector is formed of a powder compact containing first metal particles, the first metal particles each have a first protective layer disposed on at least a portion of the surface of the first metal particles, and the first protective layer comprises an oxide.
[0217] In the battery of technical solution 1, the first current collector in the first electrode is formed by a powder compact containing a first metal particle, and the first metal particle has a first protective layer containing an oxide on at least a portion of its surface. According to this structure, the first current collector can improve the corrosion resistance to gas components and solvents, etc. in the current collector formed by pressing the powder, and as a result, the reliability of the current collector can be improved. As a result, the battery of technical solution 1 can improve the reliability in the battery having a current collector formed by pressing the powder. Furthermore, since the first current collector is formed by a powder compact, the first current collector is less likely to be damaged during handling compared to a current collector formed by a thin film of metal foil, etc., and is not prone to warping even if it is thinned. Therefore, compared with a current collector formed by a thin film of metal foil, etc., the first current collector can improve reliability and reduce thickness. Therefore, the battery of technical solution 1 can achieve miniaturization, large capacity and high energy density. In this way, the battery of solution 1 has high reliability and can realize a thin, high-capacity, and high-energy-density battery.
[0218] (Technical Solution 2)
[0219] According to the battery according to claim 1, the first protective layer includes an oxide of a metal component constituting the first metal particles.
[0220] According to this structure, in the first metal particle, the metal portion is firmly bonded to the oxide on its surface. Therefore, in the first metal particle, the bonding property between the metal portion and the first protective layer on its surface is improved, so the first protective layer with excellent stability is maintained on the surface of the first metal particle. Thus, a battery with further improved reliability can be provided.
[0221] (Technical Solution 3)
[0222] According to the battery described in claim 1 or 2, the first protective layer includes a metal oxide containing at least one selected from the group consisting of Al, Zr, Ti and Si.
[0223] According to this structure, the corrosion resistance of the first protective layer can be further improved. Therefore, a battery with further improved reliability can be provided.
[0224] (Technical Solution 4)
[0225] According to the battery described in any one of claims 1 to 3, the first protective layer includes an amorphous body.
[0226] According to this structure, the first protective layer becomes softer than when it is composed only of a crystalline body. Therefore, the first protective layer is easily plastically deformed. Therefore, when the first metal particles are pressurized during the formation of the powder compact, friction is reduced, the sliding between the particles is improved, and the density of the powder compact is improved. In addition, when the powder compact is formed, the easily deformable first protective layer is easily squeezed and moved from the bonding interface between the particles to the voids in the powder compact. Thus, the component of the first protective layer filling the voids can be increased, and the exposed surface of the first metal particles can be reduced. Therefore, the corrosion resistance of the first current collector is further improved, so a battery with further improved reliability can be provided.
[0227] (Technical Solution 5)
[0228] According to the battery according to any one of claims 1 to 4, the first protective layer includes two or more oxides having different compositions from each other.
[0229] According to this structure, the corrosion resistance of the first protective layer to various gases and the like is improved, so that a battery with further improved reliability can be provided.
[0230] (Technical Solution 6)
[0231] According to the battery described in any one of claims 1 to 5, the first protective layer is composed of a multilayer film including two or more layers.
[0232] According to this structure, the corrosion resistance of the first protective layer to various gases and the like is improved, so a battery with further improved reliability can be provided. In addition, during the pressurization process of forming the powder compact, the friction between the first metal particles can be changed. For example, a soft film can also be formed on the outermost surface to reduce friction. Therefore, the compactness of the powder compact can be improved. Thus, a first current collector with low resistance and high reliability can be achieved, so a battery with further improved reliability can be provided.
[0233] (Technical Solution 7)
[0234] According to the battery described in any one of technical solutions 1 to 6, in the compressed powder body, the volume of the first protective layer is larger in the second region which is the void portion of the grain boundary triple point of the first metal particles than in the first region which is the bonding interface of two adjacent first metal particles.
[0235] According to this structure, the electrical bonding of the bonding interface between the first metal particles can be further achieved. In addition, by having a large amount of the first protective layer in the second region of the void portion which is the grain boundary triple point of the first metal particle, the composition of the first protective layer filling the void portion can be increased. Therefore, the exposed surface of the first metal particle is reduced. Thus, the first current collector with suppressed resistance loss and further improved corrosion resistance can be achieved, so a high-performance battery with further improved reliability can be provided.
[0236] (Technical Solution 8)
[0237] According to the battery according to any one of claims 1 to 7, the powder compact further includes second metal particles, and the second metal particles include a metal different from a metal forming the first metal particles.
[0238] This structure allows various control of the properties of the first current collector. For example, by selecting the second metal particles, a first current collector having properties such as mechanical properties, electrochemical properties, and thermal expansion coefficient that cannot be obtained by a single-composition metal material can be obtained.
[0239] (Technical Solution 9)
[0240] According to the battery described in claim 8, the average particle size of the second metal particles is smaller than the average particle size of the first metal particles.
[0241] According to this structure, the second metal particles are easily filled into the gaps between the first metal particles, and a dense first current collector containing a composite metal material can be obtained, wherein the composite metal material contains the first metal particles and the second metal particles. Therefore, a first current collector with suppressed resistance loss can be realized, so a higher performance battery can be provided.
[0242] (Technical Solution 10)
[0243] According to the battery according to claim 8 or 9, each of the second metal particles has a second protective layer provided on at least a portion of the surface of the second metal particle.
[0244] This structure can realize a first current collector with higher reliability, and thus can provide a battery with further improved reliability.
[0245] (Technical Solution 11)
[0246] According to the battery according to claim 10, the second protective layer is formed of a material having a composition different from that of the first protective layer.
[0247] According to this structure, the first current collector can be further provided with corrosion resistance to gas components different from the gas components etc. exhibiting corrosion resistance to the first protective layer. Therefore, a first current collector having better stability against various gas components can be obtained, so a battery with further improved reliability can be provided.
[0248] (Technical Solution 12)
[0249] According to the battery described in claim 10 or 11, the second protective layer has a thickness different from that of the first protective layer.
[0250] According to this structure, the first current collector can be further given corrosion resistance to gas components different from the gas components that exhibit corrosion resistance in the first protective layer within a wider range of conditions. Therefore, a first current collector with better stability relative to various gas components can be obtained, so a battery with further improved reliability can be provided. In addition, for example, by appropriately adjusting the deformability and friction of the second protective layer, the compactness of the powder body can also be controlled. Thus, a first current collector with low resistance and high reliability can be achieved, so a battery with further improved reliability can be provided.
[0251] (Technical Solution 13)
[0252] According to the battery described in any one of claims 8 to 12, the second metal particles have a hardness different from that of the first metal particles.
[0253] According to this structure, the microstructure of the composite metal material containing the first metal particles and the second metal particles can be controlled, so the filling property by pressurizing the powder compact can be controlled. Therefore, the density and mechanical properties of the first current collector can be controlled.
[0254] (Technical Solution 14)
[0255] According to the battery described in claim 13, the second metal particles are softer than the first metal particles.
[0256] According to this structure, in the powder compact when pressurized, the second metal particles are deformed and filled first to fill the gaps between the first metal particles. Therefore, the density of the composite metal material containing the first metal particles 111 and the second metal particles is improved, so that a first current collector with high conductivity and high corrosion resistance can be achieved. In addition, the second metal particles in the composite metal material absorb the stress caused by the thermal expansion of the first metal particles 111 and the charge and discharge. Therefore, a first current collector with high durability in cold and hot cycles and charge and discharge cycles can be obtained.
[0257] (Technical Solution 15)
[0258] According to the battery described in claim 13, the second metal particles are harder than the first metal particles.
[0259] According to this structure, in the powder compact when pressurized, a fine structure including the second metal particles embedded in the first metal particles between the first metal particles 111 can be formed. Therefore, the second metal particles act as anchors connecting the first metal particles to each other, so the bonding between the first metal particles is enhanced. As a result, the durability of the first current collector with respect to bending (e.g., bending) stress and processing is improved, so the mechanical reliability of the first current collector is improved.
[0260] (Technical Solution 16)
[0261] According to the battery according to any one of claims 8 to 15, the second metal particles have a different potential from that of the first metal particles.
[0262] According to this structure, the electrochemical stability of the first current collector can be adjusted. In addition, for example, by configuring the first metal particles and the second metal particles in layers, the first current collector can be made into a two-layer structure, and the electrochemical stability can be adjusted to be different on the upper and lower surfaces of the first current collector. Therefore, the electrochemical stability of the current collector can be controlled in accordance with the working potential or charge and discharge voltage of the active material. Therefore, a highly reliable and high-performance battery can be achieved.
[0263] (Technical Solution 17)
[0264] According to the battery according to any one of claims 1 to 16, the first metal particles are composite metal particles containing a plurality of metals having different compositions.
[0265] According to this structure, the first current collector can control characteristics such as corrosion resistance, thermal expansion, electrochemical stability, and mechanical reliability, thereby achieving a high-performance and highly reliable battery.
[0266] (Technical Solution 18)
[0267] According to the battery according to any one of claims 1 to 17, the first metal particles are composite metal particles containing a plurality of metals having different potentials from each other.
[0268] According to this structure, the electrochemical stability can be controlled in the first current collector, so that a high-performance and highly reliable battery can be realized.
[0269] (Technical Solution 19)
[0270] In the battery according to any one of claims 1 to 18, the first current collector further contains a resin component.
[0271] According to this structure, the mechanical strength of the first current collector and the bonding property with the first active material layer are enhanced, so that a battery having high reliability against external stress such as bending and impact can be obtained.
[0272] (Technical Solution 20)
[0273] According to the battery described in any one of claims 1 to 20, the first current collector includes at least one selected from a Si-containing component and a F-containing component.
[0274] According to this structure, a first current collector having high heat resistance and corrosion resistance can be realized. In addition, for rapid temperature changes, the difference in thermal expansion coefficient of the bonding interface between the Si-containing component or the F-containing component (e.g., the resin component) and the first metal particle can be absorbed by the flexibility of the Si-containing component or the F-containing component. Therefore, the Si-containing component or the F-containing component is not easily peeled off from the first current collector, and the high heat resistance and corrosion resistance of the first current collector can be maintained. Therefore, a battery with high reliability for the heat generation of the battery caused by high-rate operation such as rapid charging and discharging can be realized.
[0275] (Technical Solution 21)
[0276] According to the battery described in claim 20, the total volume concentration of the Si-containing component and the F-containing component is higher at the interface between the first current collector and the first active material layer than inside the first current collector.
[0277] According to this structure, the reliability of the interface between the first current collector and the first active material layer, which has the highest ion movement density and easily generates heat, is improved, so that a battery with further improved reliability can be obtained.
[0278] (Technical Solution 22)
[0279] The battery according to any one of claims 1 to 21 comprises an electrolyte layer, the electrolyte layer contains the electrolyte, and is disposed between the first electrode and the second electrode, wherein the electrolyte is a solid electrolyte.
[0280] According to this structure, a battery with further improved reliability can be obtained.
[0281] The battery of the present disclosure is described above based on the embodiments, but the present disclosure is not limited to these embodiments. As long as it does not depart from the main purpose of the present disclosure, various modifications that a person skilled in the art may think of in the embodiments, or other schemes constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present disclosure.
[0282] In addition, various changes, substitutions, additions, omissions, etc. can be made to the above-described embodiments within the scope of the claims or the scope equivalent thereto.
[0283] Industrial Availability
[0284] The battery disclosed herein can be used for secondary batteries such as all-solid batteries used in various electronic devices, automobiles, and the like.
[0285] Description of Reference Numerals
[0286] 100 1st electrode
[0287] 110, 114, 115 1st current collector
[0288] 111 No.1 Metal Particle
[0289] 112 1st protection layer
[0290] 113 2nd Metal Particle
[0291] 120 first active material layer
[0292] 200 2nd electrode
[0293] 210, 214, 215 Second collector
[0294] 220 second active material layer
[0295] 300 Solid electrolyte layer
[0296] 400 Overlay
[0297] 500a, 500b terminal electrodes
[0298] 600 Bipolar Electrode
[0299] 1000, 1001, 1002, 1003, 1004, 1005 batteries
Claims
1. A battery comprising a first electrode, a second electrode and an electrolyte, The first electrode includes a first current collector and a first active material layer. The first current collector is formed of a powder compact containing first metal particles. The first metal particles each have a first protective layer provided on at least a portion of the surface of the first metal particle. The first protective layer includes oxide.
2. The battery according to claim 1, The first protective layer includes an oxide of a metal component constituting the first metal particles.
3. The battery according to claim 1, The first protective layer includes a metal oxide containing at least one selected from the group consisting of Al, Zr, Ti, and Si.
4. The battery according to claim 1, The first protective layer includes an amorphous body.
5. The battery according to claim 1, The first protective layer includes two or more oxides having different compositions from each other.
6. The battery according to claim 1, The first protective layer is composed of a multilayer film including two or more layers.
7. The battery according to claim 1, In the powder compact, the volume of the first protective layer is larger in the second region which is a void portion of a triple point of a grain boundary of the first metal particles than in the first region which is a bonding interface between two adjacent first metal particles.
8. The battery according to claim 1, The powder compact further contains second metal particles. The second metal particles include a metal different from a metal forming the first metal particles.
9. The battery according to claim 8, The average particle size of the second metal particles is smaller than the average particle size of the first metal particles.
10. The battery according to claim 8, Each of the second metal particles has a second protective layer provided on at least a portion of a surface of the second metal particle.
11. The battery according to claim 10, The second protective layer is formed of a material having a composition different from that of the first protective layer.
12. The battery according to claim 10, The second protective layer has a thickness different from that of the first protective layer.
13. The battery according to claim 8, The second metal particles have a hardness different from that of the first metal particles.
14. The battery according to claim 13, The second metal particles are softer than the first metal particles.
15. The battery according to claim 13, The second metal particles are harder than the first metal particles.
16. The battery according to claim 8, The second metal particles have a different potential from that of the first metal particles.
17. The battery according to claim 1, The first metal particles are composite metal particles including a plurality of metals having different compositions from each other.
18. The battery according to claim 1, The first metal particles are composite metal particles including a plurality of metals having different electric potentials from each other.
19. The battery according to claim 1, The first current collector further includes a resin component.
20. The battery according to claim 1, The first current collector includes at least one selected from a Si-containing component and a F-containing component.
21. The battery according to claim 20, The total volume concentration of the Si-containing component and the F-containing component is higher at the interface between the first current collector and the first active material layer than inside the first current collector.
22. The battery according to claim 1, comprising an electrolyte layer, The electrolyte layer includes the electrolyte, and is disposed between the first electrode and the second electrode. The electrolyte is a solid electrolyte.
Citation Information
Patent Citations
All-solid battery and its manufacturing method
JP2009193802A